2016
DOI: 10.17795/icrj-10(1)1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Ryanodine Receptor Calcium Channels (RyR2) in Rats with Induced Diabetes after 4 Weeks of High Intensity Interval Training

Abstract: A B S T R A C TBackground: To date, not sufficient information is available regarding the effect of High Intensity Interval Training (HIIT) on diabetes-induced myocardial dysfunctions. Objectives: The present study aimed to evaluate the effect of 4-week HIIT on change in expression levels of ryanodine receptor calcium channel (RyR2) and ATPase calcium pump (SERCA2a) in diabetic rats. Materials and Methods:This study was conducted on 24 Wistar rats with average weight of 245 ± 10 g. The rats were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Moreover, the disturbed mitochondrial performance is involved in the DCM pathophysiological mechanisms, which could be regulated with PGC-1 [ 19 ]. Other signaling pathway activations like the AMPK in response to energetic demand and calcium-based myocardial performance mediated by RyR2 and SERCA2 are among the implicated parameters in DCM [ 10 , 25 ]. The exercise protocols might alleviate cardiovascular complications and mitigate DCM incidence by preventing pathological cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the disturbed mitochondrial performance is involved in the DCM pathophysiological mechanisms, which could be regulated with PGC-1 [ 19 ]. Other signaling pathway activations like the AMPK in response to energetic demand and calcium-based myocardial performance mediated by RyR2 and SERCA2 are among the implicated parameters in DCM [ 10 , 25 ]. The exercise protocols might alleviate cardiovascular complications and mitigate DCM incidence by preventing pathological cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Severe systolic dysfunction was also demonstrated in diabetic patients, which might be related to the alteration of gene expression involved in adjusting intracellular calcium homeostasis. The changeover of calcium-based activities such as RyR2 and SERCA2a sensitivity change in diabetesis somewhat responsible for the myocardial contraction disturbance [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also reported that susceptibility of myocardial cells to calcium in inactive people or patients with cardiac functional disorder reduces. This reduction is associated with downregulation of hydroxypyridine and ryanodine receptors as well as myocardial sarco/endoplasmic reticulum Ca 2+ ATPase pumps (SERCA) (35). After sporting activities based on Cardiac Rehab, these recipients are upregulated and thus, the susceptibility of the myocardial cells to calcium will increase; so, heart contractility power increases with each hit compared to before rehab program.…”
Section: Discussionmentioning
confidence: 99%